THE SHIFTING FROM THE MALE GAZE TO THE FEMALE GAZE IN K-POP GIRL GROUPS AS THE IMPACT OF #METOO MOVEMENT IN SOUTH KOREA - Varianna, Enya Achresia; Kusumawardani, Natasya (Indonesian Association for International Relations, 2024)
This research analyses the shift from the male gaze to the female gaze in K-pop girl groups impacted by the #MeToo movement in South Korea. The shift is marked by the thriving of women empowerment ideas by girl groups. This research uses the Transnational Advocacy Network (TAN) and postfeminism, examined using qualitative research methodology with secondary and textual analysis. This research finds that the shifting from the male gaze to the female gaze in K-pop girl groups occurred through the shift from objectification to subjectification of women, focusing on individualism, choice, and empowerment, as well as showing irony and knowingness. Therefore, the #MeToo movement has impacted the K-pop industry because the gaze has shifted, and Korean society has started to accept idols supporting women's empowerment and gender equality